PSX-5 Evidences of mitochondrial dysfunction and oxidative stress in newly weaned piglets. (7th December 2018) - Kétilim-Novais, A; Roy, C; Beaulieu, S; Martel-Kennes, Y; Lessard, M; Matte, J; Lapointe, J
Abstract: The period following weaning is characterised by a high incidence of nutritional stress, intestinal disturbances and bacterial infections that led to serious diseases. Mounting evidence indicates that mitochondrial function and oxidative stress are closely related to cellular energetic efficiency, immune response and bacterial pathogenesis. The objective of this study was thus to characterize markers of mitochondrial energy metabolism and oxidative stress status throughout the peri-weaning period. To conduct the study, 30 multiparous sows were inseminated, and litters were standardized to 12 piglets. Selected piglets were assigned to one of two experimental groups: normal birth weight piglets (NBW, 1, 67 ± 0, 08 kg, n = 60) and low birth weight piglets (LBW, 1, 09 ± 0, 01 kg, n = 60). Then, 10 piglets from each group were selected at 14, 21 (weaning), 23, 25, 29 and 35 days of age to collect plasma and organ (liver, intestinal mucosa and kidney) samples. Analysis revealed a significant increase (P < 0.05) in the levels of both oxidative damage to DNA (8-hydroxy-2'-deoxyguanosine, 8-OHdG) and proteins (carbonyls) measured in plasma after weaning. A significant decrease (P < 0.05) in cellular energy level in the form of adenosine triphosphate (ATP) content, known to be produced in mitochondria, was observed in the liver after weaning. This decrease was found to be linked to significantly higher (P < 0.05) mitochondrial activity of major antioxidant glutathione peroxidase (GPx) and superoxide dismutase (SOD) in liver, intestinal mucosa and kidneys of piglets following weaning. Additionally, the level of 8-OHdG in plasma and the concentration of protein carbonyls in liver were found to be higher (P < 0.05) in LBW piglets. These results demonstrate that weaning induces mitochondrial dysfunction and oxidative stress in piglets after weaning and indicate that LBW piglets are more severely affected than their NBW littermates.